2015
DOI: 10.1016/j.fertnstert.2015.07.920
|View full text |Cite
|
Sign up to set email alerts
|

Predictors for sperm retrieval in microdissection sperm extraction for non-obstructive azoospermia

Abstract: formulations. 42 (48.3%) used cutaneous testosterone gels, while 23 (26.4%) used testosterone injections. 49 (56.3%) respondents found their patients to be satisfied ''most times'' and 30 (34.5%) said their patients are ''almost always'' satisfied with Testopel therapy. When Testopel therapy was discontinued, cost was cited as the most common reason.CONCLUSIONS: Testopel implantation appears to be a highly successful therapy for the treatment of hypogonadism. This study categorizes common practices that have y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…serum FSH level, testicular volume and age, each having a correlation with the testicular sperm retrieval rate (Carpi, et al , 2009, Turunc, et al , 2010, Cissen et al , 2016). However, it is notable that FSH was found not to be correlated with the sperm acquisition rate in a retrospective study including 1275 patients with NOA using micro-TESE combined with ICIS (Ishikawa, et al , 2015). It is possible that in most micro-TESE series with fully detailed dissections, small, focal areas of sperm production can be found that may be missed with FNA.…”
Section: Discussionmentioning
confidence: 98%
“…serum FSH level, testicular volume and age, each having a correlation with the testicular sperm retrieval rate (Carpi, et al , 2009, Turunc, et al , 2010, Cissen et al , 2016). However, it is notable that FSH was found not to be correlated with the sperm acquisition rate in a retrospective study including 1275 patients with NOA using micro-TESE combined with ICIS (Ishikawa, et al , 2015). It is possible that in most micro-TESE series with fully detailed dissections, small, focal areas of sperm production can be found that may be missed with FNA.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, they obtained cutoff points of 400 ng/mL for total testosterone and 11 pg/mL for free testosterone with predictive accuracies of 37.7% and 35.5%, respectively. By contrast, the majority of studies analyzed both total and free levels of serum testosterone in the aforementioned groups of patients did not corroborate this statistically significant difference between the groups and therefore have concluded that serum testosterone lacks any value in predicting sperm retrieval rate by TESE operation [14,18,19,23,27,30]. Moreover, in reports which proposed testosterone as a predictive biomarker, serum testosterone level either acts as a part of a multivariate model or lacks sufficient sensitivity and specificity required for clinical application.…”
Section: Testosteronementioning
confidence: 96%
“…Similarly, Bonarriba et al [25] have introduced the cutoff point of 12.2 mIU/mL for serum FSH with sensitivity and specificity of 71% and 75%, respectively. Nevertheless, it is generally accepted that the serum FSH has a poor value for predicting the existence of sperm in the testes [27,28,30]. Indeed, cases with even serum FSH > 90 mIU/mL but positive TESE outcomes have been observed in previous studies [21].…”
Section: Follicle-stimulating Hormonementioning
confidence: 99%
See 2 more Smart Citations